Too young to leave the nest? The effects of school starting age - Sandra E. Black; Paul J. Devereux; Kjell G. Salvanes (Institute for the Study of Labor (IZA), 2008)
Does it matter when a child starts school? While the popular press seems to suggest it does, there is limited evidence of a long-run effect of school starting age on student outcomes. This paper uses data on the population of Norway to examine the role of school starting age on longer-run outcomes such as IQ scores at age 18, educational attainment, teenage pregnancy, and earnings. Unlike much of the recent literature, we are able to separate school starting age from test age effects using scores from IQ tests taken outside of school, at the time of military enrolment, and measured when students are around age 18. Importantly, there is variation in the mapping between year and month of birth and the year the test is taken, allowing us to distinguish the effects of school starting age from pure age effects. We find evidence for a small positive effect of starting school younger on IQ scores measured at age 18. In contrast, we find evidence of much larger positive effects of age at test, and these results are very robust. We also find that starting school younger has a significant positive effect on the probability of teenage pregnancy, but has little effect on educational attainment of boys or girls. There appears to be a short-run positive effect on earnings of beginning school at a younger age; however, this effect has essentially disappeared by age 30. This pattern is consistent with the idea that starting school later reduces potential labor market experience at a given age for a given level of education; however, this becomes less important as individuals age
urn:nbn:de:101:1-2008042191
Keywords: J1; 330; Education; earnings; IQ; teenage childbearing; Schüler; Altersgruppe; Bildungsertrag; Kognition; Erwerbsverlauf; Schwangerschaft; Norwegen